Toxicity assessment of nano‐TiO2 in Apis mellifera L., 1758: histological and immunohistochemical assays. Issue 4 (27th November 2019) - Ferrara, Giulia; Salvaggio, Antonio; Pecoraro, Roberta; Scalisi, Elena Maria; Presti, Andrea Maria; Impellizzeri, Giuliana; Brundo, Maria Violetta
Abstract: The aim of this study was to evaluate the toxicity of titanium dioxide nanoparticles (TiO2 NPs) by short‐term toxicity tests in Apis mellifera, considered an excellent bioindicator organism mainly due to its sensitivity. Bees have been exposed to several concentrations of TiO2 NPs (1 × 10 −3, 1 × 10 −4, 1 × 10 −5, 1 × 10 −6 mg/10 ml) for 10 days. Morphostructural and histological assays were done on gut and honey sac. The research of exposure biomarkers like metallothioneins 1 (MT1) and Heat Shock Protein 70 (HSP70) was performed to verify if a detoxification mechanism has been activated in the exposed animals. No histological alteration on the epithelium of the gut and honey sac were observed in exposed samples. A significant positivity for anti‐MT1 antibody was observed only in the honey sac cells. A weak positivity for HSP70 was observed in both structures analyzed. In several studies have shown the non‐toxicity of TiO2 NPs on other model organisms, in our study, titanium dioxide nanoparticles was proven to be highly toxic at the highest concentration tested (100% of lethality to 1 × 10 −3 mg/10 ml) and moderately toxic at lower concentrations. Honey bees proved to be excellent models for study of NPs toxicity and for monitoring environment. Abstract : Apidae are excellent bioindicators. Honey sac is involved in xenobiotics detoxification. Metallothioneins 1 are an excellent biomarkers of exposure to metallic NPs.